RECONCEPTUALIZATION OF THE SUBJECT AND OBJECT OF SCIENTIFIC RESEARCH: SOCIAL CONTEXT AND SYSTEMIC PRINCIPLES - Kubalskyi, Oleh (Bulletin of Taras Shevchenko National University of Kyiv. Philosophy, 2023)
The issue of subject-object relevance of science as an important socio-cultural phenomenon in the world of dynamic turbulence is updated. The role of science in the life of man and society is determined. An assumption is put forward regarding the content certainty of the concepts of the subject and the object of scientific knowledge in accordance with the scientific paradigms that arise in different historical eras. The fundamental connection between the level of scientific and technological development and the adequacy of cognitive scientific organizational means has been revealed. It is emphasized that at the level of the knowledge society, science is a means of resisting the phenomena of social turbulence. The specific interaction of the subject and the object of scientific knowledge determines their significance, which changes during the cognitive process. The definitions of the subject of scientific knowledge and the object of scientific knowledge are mutually determined and cannot be given in advance and without reference to a certain paradigm of scientific knowledge. Scientific communication plays a decisive role in the continuity and correctness of the transmission of scientific knowledge. Science constantly communicatively clarifies the significance of the interaction between the subject and the object of scientific research as a component of scientific normativity. It was determined that discussions about the essence of science and its place in a socially turbulent society help to determine the priorities of the scientific development of modern humanity, the key problems of scientific knowledge and the prospects for their solution.